2003
DOI: 10.3727/000000003108746867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesion or Collagen Molecules on Cell Attachment, Insulin Secretion, and Glucose Responsiveness in the Cultured Adult Porcine Endocrine Pancreas: A Preliminary Study

Abstract: The effect of either adhesion or collagen molecules on cell attachment, insulin secretion, and glucose responsiveness was investigated in adult porcine pancreatic endocrine (PE) cells that were cultured for a longer term in vitro. Six different types of molecules-laminin, fibronectin, poly-L-lysine (PLL), type I collagen, gelatin, and Matrigel-were used. Approximately 2.0 × 10 5 cells per dish of each molecule type were cultured for 4 weeks. In the laminin group, the insulin accumulation was maintained at a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Both laminin and fibronectin have been shown to affect differentiation and proliferation of ␤-cells (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both laminin and fibronectin have been shown to affect differentiation and proliferation of ␤-cells (13)(14)(15).…”
mentioning
confidence: 99%
“…The importance of cell-extracellular matrix interactions for optimally regulated insulin secretion is supported by a number of studies on ␤-cells cultured on various crude matrices or their purified extracts (15)(16)(17)(18)(19)(20)(21). We have shown that isolated rat islet ␤-cells cultured on the matrix produced by 804G cells (referred to as 804G matrix) secrete twofold more insulin in response to glucose compared with cells cultured on plastic or poly-L-lysine (22,23).…”
mentioning
confidence: 99%
“…3 Similar to studies with cell-derived matrices, culture experiments with purified individual ECM proteins resulted in better islet survival and function. Collagen type IV 11 and laminin, 6 both components of the basement membrane, contributed to greater insulin release. Islets cultured on collagen type I-coated surfaces and those treated with soluble fibronectin exhibited less apoptosis and greater insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to reestablish critical extracellular matrix (ECM)-b-cell signaling may improve current islet culture techniques used between islet isolation and transplantation, as well as the design of an artificial, immunoprotective islet carrier for transplantation. Several reports have demonstrated better in vitro survival and function of islets or individual b-cells cultured on ECM-derived substrates, both cell-secreted matrices, [1][2][3][4][5][6][7][8] and individual purified ECM proteins. 6,9,[10][11][12] Islet-matrix interactions have most often been studied with insulin-producing cells cultured two-dimensionally on ECMcoated tissue culture surfaces; however, under the proper conditions, some ECM analogs, such as collagens and Matrigel, form three-dimensional (3D) gels, allowing for the entrapment of islets or individual b-cells and the study of cell-matrix interactions in three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Laminin, another non collagenous basement membrane component, is known to play a role in the maintenance of the differentiated state and in the activation of intracellular signals through integrins. 22 These components are essential for pancreatic islets viability. Indeed, islet cells require signals from the basal membrane extracellular matrix proteins are known to mediate, through integrins, cell adhesion and are involved in a number of cellular processes, including insulin expression and secretion in pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%